Anodic and Cathodic Extracellular Electron Transfer by the Filamentous Bacterium Ardenticatena maritima 110S - Kawaichi, Satoshi; Yamada, Tetsuya; Umezawa, Akio; McGlynn, Shawn E.; Suzuki, Takehiro; Dohmae, Naoshi; Yoshida, Takashi; Sako, Yoshihiko; Matsushita, Nobuhiro; Hashimoto, Kazuhito; Nakamura, Ryuhei (Frontiers in Microbiology, 2018)
Ardenticatena maritima strain 110S is a filamentous bacterium isolated from an iron-rich coastal hydrothermal field, and it is a unique isolate capable of dissimilatory iron or nitrate reduction among the members of the bacterial phylum Chloroflexi. Here, we report the ability of A. maritima strain 110S to utilize electrodes as a sole electron acceptor and donor when coupled with the oxidation of organic compounds and nitrate reduction, respectively. In addition, multicellular filaments with hundreds of cells arranged end-to-end increased the extracellular electron transfer (EET) ability to electrodes by organizing filaments into bundled structures, with the aid of microbially reduced iron oxide minerals on the cell surface of strain 110S. Based on these findings, together with the attempt to detect surface-localized cytochromes in the genome sequence and the demonstration of redox-dependent staining and immunostaining of the cell surface, we propose a model of bidirectional electron transport by A. maritima strain 110S, in which surface-localized multiheme cytochromes and surface-associated iron minerals serve as a conduit of bidirectional EET in multicellular filaments.